Maturação sexual em bezerras nelore com suplementação alimentar: Maria Carolina Villani Miguel. - - Miguel, Maria Carolina Villani [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to evaluate the gonadotropins concentration from birth to weaning, follicular characteristics ( diameter and total number of follicles and follicular waves ) and plasma leptin from birth to first ovulation of Nelore heifers supplemented with ground corn (1.5- 2% body weight/animal/day). Twelve Nelore heifers, born with an average of 33 ± 3.08 kg, were divided into two groups: Treated (TG, n=6; receiving supplementation) and Control (CG, n = 6; without supplementation). After weaning, at five months, heifers in both groups received the same basal and the calves of the TG were added 1.5 to 2 % body weight / animal / day of ground corn. From the 18th day of life were performed ovarian evaluations in each every four days until the first ovulation to analyze the follicular characteristics. Additionally, were held every two months, daily evaluations for consecutive 17 days in order to monitoring the follicular waves. Concomitantly to ovarian evaluations were collected venous blood samples for plasma LH, FSH, leptin and progesterone quantification. The plasma concentration of leptin increased in TG th th th th at 13 , 14 , 16 and 17 month of life Five TG heifers ovulated at 17.8 ± 1.1 months and one CG heifer ovulated to 20.1 months. Based on these results it could be concluded that supplementation with ground corn anticipated age at first ovulation and increased plasma leptin from five months before the first ovulation
Keywords: Bovino; Puberdade; Ovarios; Gonadotrofinas; Leptina; Novilho; Ovulação; Weaning